Proteomics applied to pediatric medicine: opportunities and challenges. (1st September 2016) - Faa, Gavino; Messana, Irene; Fanos, Vassilios; Cabras, Tiziana; Manconi, Barbara; Vento, Giovanni; Iavarone, Federica; Martelli, Claudia; Desiderio, Claudia; Castagnola, Massimo
ABSTRACT: Introduction : Care in pediatrics often refers to treatments directed to adults. However, childhood is a specific life period, with molecular pathways connected to development and thereby it requires distinctive considerations and special treatments under disease. Proteomics can help to elucidate the molecular mechanisms underlying the human development and disease onset in pediatric age and this review is devoted to underline the results recently obtained in the field. Areas covered : The contribution of proteomics to the characterization of physiological modifications occurring during human development is presented. The proteomic studies carried out to elucidate the molecular mechanisms underlying different pediatric pathologies and to discover new markers for early diagnosis and prognosis of disease, comprising genetic and systemic pathologies, sepsis and pediatric oncology are thereafter reported. The investigations concerning milk composition in human and farm mammals are also presented. Finally, the chances offered by the integration of different -omic platforms are discussed. Expert commentary : The growing utilization of holistic technologies such as proteomics, metabolomics and microbiomics will allow, in the near future, to define at the molecular level the complexity of human development and related diseases, with great benefit for future generations.